HUBUNGAN ANTARA LINGKUNGAN KERJA DAN PENGHARGAAN (REWARD) DENGAN KOMITMEN GURU SEKOLAH DASARSE-GUGUS 3 UPTD SIAK HULU KABUPATEN KAMPAR - ELVINA ELVINA; ISJONI ISJONI; HADRIANA HADRIANA (Universitas Riau, 2017)
In accordance with the hypothesis, then the purpose of this study was to obtaininformation the relationship between the working environment and reward with a commitmentof elementary school teachers Se-Cluster 3 UPTD Siak Hulu Kabupaten Kampar. Beforereaching these objectives need to be done or known, among other things: 1) To obtain informationthat is valid and reliable relationship between the work environment and the commitment ofelementary school teachers Se-Cluster 3 UPTD Siak Hulu Kabupaten Kampar?, 2) To obtaininformation valid and reliable about the relationship between reward with a commitment ofelementary school teachers Se-Cluster 3 UPTD Siak Hulu Kabupaten Kampar?, and 3) Toobtain information valid and reliable about the relationship between the working environmentand reward together with commitment Elementary School teacher Se-Cluster 3 UPTD SiakHulu Kabupaten Kampar?. By distributing questionnaires to 114 samples Elementary Schoolteacher Se-Cluster 3 UPTD Siak Hulu Kabupaten Kampar.The results of research such is apositive relationship between the work environment (X1) with the commitment (Y). This meansthat the stronger the Working Environment, the stronger the commitment of teachers. There isa positive relationship between the reward (X2) with the commitment (Y). Means the better thereward, the stronger the commitment of teachers. There is a positive relationship between theworking environment and reward together with the commitment of teachers.Test resultssimultaneous significance that the working environment and the award together significantinfluence with the commitment of Elementary School teacher Se-Cluster 3 UPTD Siak HuluKabupaten Kampar. While the statistical test T with the results of the work environment (X1)significantly affects commitment Elementary School teacher Se-Cluster 3 UPTD Siak HuluKabupaten Kampar. While the reward (X2) significantly affects commitment Elementary Schoolteacher Se-Cluster 3 UPTD Siak Hulu Kabupaten Kampar.